(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2018)
PLAIO is pleased to include this text of Alan Mandell’s opening plenary for the 2017 National Institute on the Assessment of Adult Learning. The annual National Institute on the Assessment of Adult Learning, presented by Thomas Edison State University, was held in Atlantic City, New Jersey, on November 14-16, 2017. The theme was: “The Art & Science (and Business) of PLA.” There were two keynote speakers. Jon Talbot from the Centre for Work Related Studies at the University of Chester (UK) gave a talk called, “Past, Present and Future: Integrating Prior, Current and Future-Oriented Experiential Learning into a Personalized Curriculum.” Alan Mandell from SUNY Empire State College gave a talk called, “Celebrating … with a Pause.” Mandell’s remarks are included here. Note Special thanks to Alan Mandell and the National Institute on the Assessment of Adult Learning for allowing us to share this resource with our readers.